Telesurgery Robotics and Easy Access to Quality Healthcare Services - Alrabiee, Hanan; Alahmari, Falaa; Altowairqi , Amani (International Journal of Innovative Research in Medical Science, 2023)
Background: Due to the existing shortage of surgeons as well as other conditions that limit access to affordable and quality surgical care, there is an increasing need to embrace alternative technologies, such as telesurgery, that provide the flexibility, reach and quality desired. Objective: To evaluate the role of telesurgery in improving efficiency and increasing access to delivery of quality surgical healthcare services, as well as to stimulate the adoption of telesurgery in increasing access to quality surgical healthcare services. Research Design and Methodology: The study employed a descriptive design and was qualitative in nature. This involved a review of 29 peer-reviewed literature published on various topics on telesurgery. Research Findings and Limitations: The study established that telesurgery can help deal with the shortage of surgeons, eliminate the geographical barriers that hinder access to healthcare, and also improve the time access to affordable and quality surgical care through enhanced surgical accuracy. The study is limited to the available number of relevant peer-reviewed scholarly articles on telesurgery. Discussion and Conclusion: The research indicated significant potential in enhancing access to affordable and quality surgical healthcare. However, challenges due to high initial costs of equipment and staff training, as well as lack of adequate legal support, limit the possible adoption of telesurgery. Therefore, to mitigate the slow uptake of telesurgery, there is a need to have goodwill from relevant policy developers so that they can create a favorable legal framework to accelerate the development and uptake of telesurgery.